How transform in product `cos((3x)/2)+cos((7x)/2)+cosx` ?



Asked on

1 Answer | Add Yours

justaguide's profile pic

Posted on (Answer #1)

The sum `cos((3x)/2)+cos((7x)/2)+cosx` has to be transformed to product form.


= `2*cos(((3x)/2+(7x)/2)/2)*cos(((3x)/2-(7x)/2)/2) + cos x `

= `2*cos((10x)/4)*cos((-4x)/4) + cos x`

= `2*cos ((5x)/2)*cos -x + cos x`

= `cos x*(1 - 2*cos ((5x)/2))`

The product form is `cos x*(1 - 2*cos ((5x)/2))`

We’ve answered 287,366 questions. We can answer yours, too.

Ask a question